CD22-Binding Synthetic Sialosides Regulate B Lymphocyte Proliferation Through CD22 Ligand-Dependent and Independent Pathways, and Enhance Antibody Production in Mice - Matsubara, Naoko; Imamura, Akihiro; Yonemizu, Tatsuya; Akatsu, Chizuru; Yang, Hongrui; Ueki, Akiharu; Watanabe, Natsuki; Abdu-Allah, Hajjaj; Numoto, Nobutaka; Takematsu, Hiromu; Kitazume, Shinobu; Tedder, Thomas F.; et al. (Frontiers in Immunology, 2018)
Sialic acid-binding immunoglobulin-like lectins (Siglecs) are expressed in various immune cells, and most of them carry signaling functions. High affinity synthetic sialoside ligands have been developed for various Siglecs. Therapeutic potentials of the nanoparticles and compounds that contain multiple numbers of these sialosides and other reagents such as toxins and antigens have been demonstrated. However, whether immune responses can be regulated by monomeric sialoside ligands has not yet been known. CD22 (also known as Siglec-2) is an inhibitory molecule preferentially expressed in B lymphocytes (B cells) and is constitutively bound and functionally regulated by α2,6 sialic acids expressed on the same cell (cis-ligands) and exogenous α2,6 sialic acids (trans-ligands). Here we developed synthetic sialosides GSC718 and GSC839 that bind to CD22 with high affinity (IC50 ~100 nM), and inhibit ligand binding of CD22. When B cells are activated by B cell antigen receptor (BCR) ligation, both GSC718 and GSC839 down-regulate proliferation of B cells, and this regulation requires both CD22 and α2,6 sialic acids. This result suggests that these sialosides regulate BCR ligation-induced B cell activation by reversing ligand-mediated regulation of CD22. In contrast, GSC718 and GSC839 augment B cell proliferation induced by TLR ligands or CD40 ligation, and this augmentation requires CD22 but not α2,6 sialic acids. Thus, these sialosides appear to enhance B cell activation by directly suppressing the inhibitory function of CD22 independently of ligand-mediated regulation. Moreover, GSC839 augments B cell proliferation that depends on both BCR ligation and CD40 ligation as is the case for in vivo B cell responses to antigens, and enhanced antibody production to the extent comparable to CpG oligonuleotides or a small amount of alum. Although these known adjuvants induce production of the inflammatory cytokines or accumulation of inflammatory cells , CD22-binding sialosides do not. Thus, synthetic sialosides that bind to CD22 with high affinity modulate B cell activation through ligand-dependent and independen